Meninjau Perjalanan Perumusan Dasar Negara hingga Penetapan Dekrit Presiden 1959 - Afidah, Dahimatul (Historia Madania: Jurnal Ilmu Sejarah, 2023)
This article aims to explain how the conflicts that arose after the 1959 presidential decree. The events of the presidential decree had an important contribution to establishing the basis of the Indonesian state. The formulation of Pancasila as the basis of the state is colored by debates between national figures who have Islamic nationalist and secular nationalist thoughts. Thus giving rise to other prolonged conflicts. In uncovering how the conflict occurred at that time, researchers used historical research methods consisting of heuristics, verification and interpretation. Based on the research that has been done, it can be concluded that the journey in determining the ideology of the state ended with the enactment of the 1959 Presidential Decree by Sukarno. Since then it has been agreed that Pancasila is the legal foundation of the state and the concept of divinity that has been agreed upon is religion in accordance with their respective beliefs.